Adipose-Derived Stem Cells Facilitate Ovarian Tumor Growth and Metastasis by Promoting Epithelial to Mesenchymal Transition Through Activating the TGF-β Pathway - Liu, Xiaowu; Zhao, Guannan; Huo, Xueyun; Wang, Yaohong; Tigyi, Gabor; Zhu, Bing-Mei; Yue, Junming; Zhang, Wenjing (Frontiers in Oncology, 2021)
Adipose-derived stem cells (ADSC) are multipotent mesenchymal stem cells derived from adipose tissues and are capable of differentiating into multiple cell types in the tumor microenvironment (TME). The roles of ADSC in ovarian cancer (OC) metastasis are still not well-defined. To understand whether ADSC contributes to ovarian tumor metastasis, we examined epithelial to mesenchymal transition (EMT) markers in OC cells following the treatment of the ADSC conditioned medium (ADSC-CM). ADSC-CM promotes EMT in OC cells. Functionally, ADSC-CM promotes OC cell proliferation, survival, migration, and invasion. We further demonstrated that ADSC-CM induced EMT via TGFβ growth factor secretion from ADSC and the ensuing activation of the TGFβ pathway. ADSC-CM-induced EMT in OC cells was reversible by the TGFβ inhibitor SB431542 treatment. Using an orthotopic OC mouse model, we also provide experimental evidence that ADSC contributes to ovarian tumor growth and metastasis by promoting EMT through activating the TGFβ pathway. Taken together, our data indicate that targeting ADSC using the TGFβ inhibitor has the therapeutic potential in blocking the EMT and OC metastasis.